Potassium-doped tungsten rod for high-flexibility tungsten wire rope and manufacturing method of potassium-doped tungsten rod

Through the combination of narrow particle size potassium tungsten powder and functional agents, the problems of poor toughness and low yield at high temperatures are solved, and high-density and fine crystalline tungsten wire ropes are realized, which meets the large-size photovoltaic silicon wafers High performance requirements and reduce processing costs.

CN119282127AActive Publication Date: 2025-01-10QINGDAO HUATUNGSTEN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411415405.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Existing tungsten wire ropes have poor toughness and insufficient tensile resistance at high temperatures, and there are problems of low yield and uneven density during processing, making it difficult to meet the high performance needs of large-size photovoltaic silicon wafers.

Method used

The special high-active narrow-particle potassium-doped tungsten powder is used to prepare high-density, crystal-refined potassium-doped tungsten rods through vacuum spray doping and medium-frequency sintering. Combined with functional agents, the dopant solution is optimized to form a stable nano-scale initial Crystallization improves the high-temperature creep resistance and tensile strength of tungsten wire.

Benefits of technology

It significantly improves the yield, qualification rate and service life of tungsten wire rope, improves the high-temperature sag resistance and deformation resistance, meets the high-performance requirements of large-size photovoltaic silicon wafers for tungsten wire ropes, and reduces processing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119282127A_ABST
    Figure CN119282127A_ABST
Patent Text Reader

Abstract

The invention discloses a potassium-doped tungsten rod for a high-flexibility tungsten wire rope and a manufacturing method of the potassium-doped tungsten rod, and belongs to the technical field of powder for metal additive materials, and the manufacturing method comprises the following steps of (1) material selection, (2) pre-reduction, (3) vacuum spray doping, (4) reduction, (5) batch pickling, (6) mixing, (7) hard film cold isostatic pressing forming, (8) low-temperature impurity removal, (9) vertical melting pre-sintering and (10) medium-frequency sintering. And finally obtaining the potassium-doped tungsten rod. Compared with the prior art, the method has the advantages that the special high-activity potassium-doped tungsten powder with the narrow particle size range is adopted for producing the tungsten rod, and the potassium-doped tungsten blank obtains stable and micro-nano-scale initial crystals in the sintering of vertical melting and medium frequency combination through regulation and control of the narrow particle size range; the yield reaches 88%-90%, the percent of pass is larger than or equal to 95%, the tensile strength is larger than or equal to 2250 N / mm < 2 >, the high-temperature recrystallization temperature is 1850-2380 DEG C, the 0.39 mm specification high-temperature droop value is smaller than or equal to 1.5 mm, the length-width ratio is larger than or equal to 15, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder for metal additives, and in particular to a potassium-doped tungsten rod for high-flexibility tungsten wire rope and a manufacturing method thereof. Background Art

[0002] Tungsten wire rope is one of the important components of single crystal furnace equipment in the photovoltaic industry. It is used to stretch polysilicon in the crystal growth furnace. As photovoltaic silicon wafers develop towards larger sizes, the outer diameter of M12 silicon wafers is as high as 295mm. The weight of polysilicon in each batch increases by more than 19%. Therefore, higher performance requirements are put forward for the performance of tungsten wire rope, which are mainly manifested in: the number of tungsten wire rope windings increases from 133 19*7 structures to 532 4*19*7 structures, and is still increasing. By increasing the number of strands, the upper limit of the load-bearing capacity and tensile strength of the tungsten wire rope in the cold and hot states in the crystal growth furnace are improved; since polysilicon needs to be heated to about 1500℃ to form a single crystal, the tungsten wire rope needs to withstand the tension in the crystal direction at a temperature exceeding 1000℃ for a long time without breaking. It must have a high complete recrystallization temperature, a low vertical resistance value, and excellent high-temperature creep resistance. Based on the above performance requirements, improving the tungsten rod used to produce tungsten wire rope is one of the fastest and most effective methods. However, the tungsten wire rope produced by traditional pure tungsten rods has the disadvantages of poor toughness, low recrystallization temperature, low strength, poor high temperature anti-sagging performance and anti-creep performance, and short service life. Although the doped tungsten rods doped with rare earth elements have solved the problems of low strength, poor toughness, and low recrystallization temperature of tungsten wire rope made of pure tungsten to a certain extent, the melting point of rare earth oxides is greater than 2400℃, and the reprocessing process is solid-state extrusion and stretching. On the one hand, the growth rate of its internal stress during the processing is several times that of pure tungsten rods. On the other hand, the displacement of rare earth oxides can easily cause fibrosis in the tissue. The yield rate of wires processed to specifications below 1.0mm is greatly reduced, and there are problems such as high crack point of tungsten wire and poor toughness stability, and it cannot fully and effectively meet the requirements of tungsten wire rope for performance improvement. Traditional potassium-doped tungsten rods are developed for use as lamp wires. The density of tungsten rods is generally around 91% of the theoretical density, and the crystals of tungsten rods are relatively coarse. The high-temperature creep resistance, strength, toughness, recrystallization temperature, etc. of the tungsten wire core area of ​​0.6-1.2mm tungsten wire rope cannot meet the demand for improving the performance of tungsten wire ropes.

[0003] In the prior art, Chinese invention patent CN110526295A discloses a method for preparing ytterbium-doped potassium gadolinium tungstate nanocrystalline particles, wherein micron-sized ytterbium-doped potassium gadolinium tungstate particles are wet-milled, and then subjected to a first separation treatment to obtain first ytterbium-doped potassium gadolinium tungstate nanocrystalline particles; the first ytterbium-doped potassium gadolinium tungstate nanocrystalline particles are etched with an acid solution, and then subjected to a second separation treatment, and then washed to obtain second ytterbium-doped potassium gadolinium tungstate nanocrystalline particles; the first ytterbium-doped potassium gadolinium tungstate nanocrystalline particles are aggregated in water, and the second ytterbium-doped potassium gadolinium tungstate nanocrystalline particles are dispersed in water. The preparation method is simple and easy to operate, does not cause environmental pollution, and can control the size of nanoparticles after ball milling, and is suitable for large-scale preparation of monodispersed ytterbium-doped potassium gadolinium tungstate nanocrystalline particles; and the prepared ytterbium-doped potassium gadolinium tungstate nanocrystalline particles are stably dispersed in water. However, the high temperature creep resistance, strength, toughness and recrystallization temperature of the ytterbium-doped potassium gadolinium tungstate nanocrystalline granular feed obtained by the invention still need to be improved. Summary of the invention

[0004] In the prior art, the high density and crystallization of potassium-doped tungsten rods are a set of mutually constrained product parameters. In the conventional production process, the density of potassium-doped tungsten rods is increased, and their crystallization will coarsen. In view of the shortcomings of the prior art, how to provide a preparation method for tungsten rods for making high-flexibility tungsten wires to balance the relationship between the two, so as to obtain high-density and micron-crystalline potassium-doped tungsten rods is the basic purpose of the present invention. The tungsten wire made of this tungsten rod has high-temperature creep resistance and high strength, a higher recrystallization temperature, and stable toughness. It is a further purpose to effectively improve the processing problems of low tungsten wire production rate and low yield rate. In addition, further enabling the tungsten wire to obtain better high-temperature strength, high-temperature anti-sagging performance and anti-deformation performance, and reducing the processing cost of rods and wires, energy saving and consumption reduction is another purpose.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A method for manufacturing a potassium-doped tungsten rod for high-flexibility tungsten wire rope is as follows:

[0007] (1) Material selection

[0008] Monoclinic ammonium paratungstate and spherical ammonium paratungstate are mixed, and the obtained mixture is used as a raw material;

[0009] (2) Pre-reduction

[0010] The raw material of step (1) is pre-reduced using a reduction furnace with no less than four temperature zones to obtain ammonium tungsten bronze with cracks on the surface;

[0011] The raw material of step (1) is reduced by using a four-zone temperature reduction furnace to obtain ammonium tungsten bronze with cracks on the surface;

[0012] (3) Vacuum spray doping

[0013] It is divided into four stages as follows:

[0014] In the first stage, an appropriate amount of ammonium tungsten bronze obtained in step (2) is placed in a vacuum doping pot and evacuated to ≤500 Pa;

[0015] In the second stage, potassium hydroxide, silicic acid and aluminum nitrate solids are respectively put into water at 50-70°C to completely dissolve, and then dilute nitric acid is added, and the above solutions are continuously stirred to prepare a doping agent solution, and the temperature of the doping agent solution is heated to 40-50°C, and then slowly sprayed from the atomization hole of the vacuum doping pot, and the total amount does not exceed 1 / 3 of the rated addition amount, and the steam input valve is opened 1 / 3, and the steam pressure is controlled to be 0.1-0.2Mpa, and at this time, the materials in the pot must be turned over, and the pot body is heated with steam to keep the temperature of the materials in the furnace at 55-85°C;

[0016] In the third stage, the frequency of the pot body turning is increased, and the remaining dopant solution is sprayed in atomization within 30 to 50 minutes, the temperature in the furnace is maintained at 85 to 95°C, the steam input valve is opened 2 / 3, and the steam pressure is controlled at 0.1 to 0.2Mpa;

[0017] In the fourth stage, after the atomization spraying of all dopants is completed, the steam input valve is fully opened, the steam pressure is controlled at 0.2-0.3Mpa, the temperature in the furnace is raised to 100-120°C, and the drying is continued for 3.5 hours to evaporate all the water. When the vacuum degree in the vacuum doping pot is maintained at 400-500Mpa, the steam heating is turned off, and water cooling is performed until the temperature in the furnace reaches 50-55°C. The discharge valve is opened to pass through a 20-100 mesh sieve to obtain potassium-ammonium-doped tungsten bronze;

[0018] (4) Restore

[0019] The potassium-ammonium-doped tungsten bronze obtained in step (3) is reduced once in a hydrogen atmosphere to obtain potassium-doped tungsten powder with an average particle size of 3.0 μm to 3.2 μm;

[0020] The production state particle size distribution of the potassium-doped tungsten powder has a particle size D10 of 3.1 μm to 3.6 μm, a particle size D50 of 8.0 μm to 15 μm, and a particle size D90 of 25 μm to 32 μm;

[0021] The ground particle size distribution of the potassium-doped tungsten powder is such that the particle size D10 is 1.5 μm to 2.1 μm, the particle size D50 is 3.4 μm to 4.1 μm, and the particle size D90 is 6.5 μm to 8.2 μm;

[0022] (5) Batch pickling

[0023] The potassium-doped tungsten powder obtained in step (4) is washed with 4 mol / L dilute hydrochloric acid and 2 mL / L dilute hydrofluoric acid in sequence to remove invalid potassium and other impurities in the potassium-doped tungsten powder, and then the residual dilute hydrochloric acid and dilute hydrofluoric acid are removed with water at a temperature of 50° C. to 65° C., and finally the tungsten mud is dried in a vacuum box, and the dried tungsten mud is crushed again and passed through a sieve to obtain acid-washed potassium-doped tungsten powder;

[0024] (6) Mixing

[0025] The acid-washed potassium-doped tungsten powder obtained in step (5) is put into a high-speed mixer, mixed for 60 to 120 minutes under the protection of nitrogen, and discharged and sieved through a 150-200 mesh sieve when cooled to 40 to 50° C. to obtain a potassium-doped mixed powder;

[0026] (7) Hard film cold isostatic pressing

[0027] The potassium-doped powder obtained in step (6) is placed in a rubber hard mold sleeve with a length of 800 mm, a diameter of 25.5 mm to 27 mm, and a wall thickness of 1.8 mm to 2.2 mm according to a unit weight of 3000 g / piece to 4000 g / piece, and is vibrated and sealed and fastened. The mold sleeve is placed in a cold isostatic press and a pressing pressure of 140 MPa to 170 MPa is used to obtain a potassium-doped tungsten green body with good appearance and certain strength.

[0028] (8) Low temperature impurity removal

[0029] The potassium-doped tungsten green body obtained in step (7) is placed in a hydrogen protection furnace at 1000° C. to 1100° C. and fired for 40 min to 60 min to obtain a potassium-doped tungsten green body with improved strength;

[0030] (9) Vertical melting pre-sintering

[0031] The potassium-doped tungsten blank obtained in step (8) is placed in a vertical melting furnace and sintered under hydrogen protection to volatilize more than 95% of the impurities and reach a density of 15.5 g / cm 3 ~16.5g / cm 3 , the initial crystal size obtained on the cross section is 1.5nm~5nm;

[0032] The power-on sintering system is heating up, heating up, keeping warm, and keeping warm in sequence;

[0033] The current / time parameters are as follows: heating 0A~2800A / 5min, heating 2800A~3850A / 6min, heating 3850A~4820A / 6min, keeping warm 4820A / 21min; hydrogen flow rate is 1.8m 3 / h~2.2m 3 / h;

[0034] (10) Medium frequency sintering

[0035] The incompletely dense potassium-doped tungsten bars obtained in step (9) are placed in a medium frequency furnace, and the tungsten bars are placed vertically in a stacking firing mode. The sintering is carried out under hydrogen protection by adopting a double hydrogen introduction mode at the bottom and top of the furnace. The sintering process is automatically controlled by an infrared temperature measurement + PLC temperature control system. The sintering system is sequentially heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, and heat preservation. The temperature / time parameters are sequentially: (0-1250°C) / 430min, heat preservation: 1250°C / 90min, heating (1250 ~1500℃) / 150min, keep warm at 1500℃ / 120min, heat up (1500~1800℃) / 361min, keep warm at 1800℃ / 150min, heat up (1800~1900℃) / 180min, keep warm at 1900℃ / 150min, heat up (1900~2000℃) / 240min, keep warm at 2000℃ / 120min, heat up (2000~2050℃) / 180min, keep warm at 2050℃ / 300min.

[0036] In the material selection of step (1), monoclinic ammonium paratungstate and spherical ammonium paratungstate are mixed in a weight ratio of 4:1 to 1.5.

[0037] The ammonium tungsten bronze with cracks during the pre-reduction in step (2), wherein the cracks account for more than 75% of the total surface area of ​​the ammonium tungsten bronze.

[0038] In the step (2), the temperatures of the four temperature zones in the pre-reduction are 300°C to 330°C, 390°C to 410°C, 410°C to 430°C, and 430°C to 450°C, respectively, and the hydrogen flow rate is 0.3m 3 / h~0.4m 3 / h, the pre-reduction boat load is 720g-800g, passed through a 20-100 mesh sieve, and pushed at a speed of 10-20min.

[0039] In the second stage of the vacuum spray doping in step (3), the contents of various substances are 2 to 3 parts by weight of potassium hydroxide, 4.5 to 5.5 parts by weight of silicic acid, and 1.8 to 3 parts by weight of aluminum nitrate solids, which are completely dissolved in 50 to 70 L of water at 50 to 70° C., and then 0.5 to 2 L of dilute nitric acid is added.

[0040] In the step (3) of vacuum spray doping, low power is used for vacuuming in the second stage, the third stage and the initial stage of the fourth stage, and medium-high power is used for vacuuming in the middle and late stages of the fourth stage; wherein the low power is 25% to 35% of the output power of the vacuuming equipment, and the medium-high power is 70% to 85% of the output power of the vacuuming equipment.

[0041] The temperatures of the five temperature zones in the reduction step (4) are 660°C to 680°C, 710°C to 740°C, 790°C to 820°C, 820°C to 840°C, and 840°C to 870°C, respectively, and the hydrogen flow rate is 4m 3 / h~7m 3 / h, the boat loading amount is 350g ~ 550g, and the effective reduction time is 6h ~ 8h.

[0042] In the step (5), the batch is pickled and passed through a 150-170 mesh screen to obtain an acid-washed potassium-doped tungsten powder, wherein the effective potassium content of the acid-washed potassium-doped tungsten powder is 65ppm-80ppm.

[0043] Preferably, in the second stage of the vacuum spray doping in step (3), the contents of the substances are 2 to 3 parts by weight of potassium hydroxide, 4.5 to 5.5 parts by weight of silicic acid, 1.8 to 3 parts by weight of aluminum nitrate solid, and 0.1 to 0.3 parts by weight of the functional agent, which are completely dissolved in 50 to 70 L of water at 50 to 70 ° C, and then 0.5 to 2 L of dilute nitric acid is added;

[0044] The preparation method of the functional agent is as follows, in parts by weight:

[0045] S1, 25-35 parts of ZSM-5 molecular sieve and 35-45 parts of bentonite are mixed, and then the mixture is added to 1400-1600 parts of 80-90wt% phosphoric acid solution for impregnation treatment for 0.5-2 hours to promote the activation of the material surface; after the impregnation process is completed, the excess solution is removed by filtering and washing with water, and then drying is performed, and the dried powder is added to 1700-1900 parts of 60-80wt% ethanol aqueous solution for mixing, and then 5-7 parts of 1-octylpyridinium bromide and 8-12 parts of EDTA disodium calcium are added for treatment; after the treatment is completed, the pretreated product is obtained by filtering, washing and drying;

[0046] S2, dispersing the pretreated product obtained in step 1 in 600-800 parts of water, then adding 25-35 parts of tetraallyl silicate, 55-65 parts of diethylenetriamine and 2-4 parts of cobalt chloride to form a uniform precursor solution; treating at 90-98°C and 0.2-0.4MPa for 1-3 hours, then filtering, washing with water and drying, and then calcining at 300-500°C under a nitrogen atmosphere for 2-5 hours to obtain a post-treated product;

[0047] S3, dissolving 35-45 parts of poly 1,2-propylene glycol and 25-35 parts of methyl acetoacetate in 600-800 parts of water to form a uniform solution; adding 1-3 parts of 70-85wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 80-95°C, and the treatment time is 3-10 hours; collecting the liquid in the reactor to obtain a promoter;

[0048] S4, 30 to 50 parts of the post-treated product obtained in step S2 are mixed with 140 to 160 parts of the accelerator obtained in step S3, the pH value is adjusted to 9 to 10.5 by 10 to 18 wt % ammonia water, the treatment is carried out for 1 to 3 hours, and then the pH value is adjusted to 8 to 9 by ammonia evaporation treatment to obtain a functional agent.

[0049] Compared with the prior art, it has the following beneficial effects:

[0050] 1) The present invention adopts a special high-activity narrow-size range potassium-doped tungsten powder to produce tungsten rods, which not only eliminates the production scale effect limitation brought by the size combination powder, but also improves the cold isostatic pressing effect. More importantly, through the narrow size range regulation, in the vertical melting and medium frequency combined sintering, the vertical melting pretreatment is used to make the potassium-doped tungsten blank obtain stable, nano-scale initial crystallization, and then through the low-temperature slow sintering of the medium frequency, the density reaches 18.1g / cm 3 ~18.4g / cm 3 At the same time, the crystallization rate is controlled to make the cross-section of the potassium-doped tungsten rod reach 20,000 crystals / mm. 2 ~30000 pieces / mm 2 , the grain size is maintained at 9nm~20nm, reaching the micro-nano level.

[0051] 2) The tungsten rod product of the present invention is processed into 0.3mm-0.6mm tungsten wire, with a finished product rate of 88%-90%, a qualified rate of ≥95%, and a tensile strength of ≥2250N / mm 2 The high-temperature recrystallization temperature is 1850℃~2380℃, the high-temperature sag value of 0.39mm specification is ≤1.5mm, the aspect ratio is ≥15, and at the same time, it has good high-temperature creep resistance. All parameters are completely superior to the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. The service life of the finished tungsten wire rope is more than 20% higher than the same type of products on the market.

[0052] 3) The addition of functional agents in the present invention can further improve the comprehensive performance of the doped tungsten rod, including enhancing the density and grain refinement of the material, improving the uniformity of the potassium content and the mechanical strength of the product, so that the final tungsten wire rope exhibits higher flexibility, tensile strength and high-temperature stability. These improvements significantly increase the service life of the tungsten wire rope compared to existing products on the market. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is the potassium-doped tungsten rod prepared in Example 1. DETAILED DESCRIPTION

[0054] ZSM-5 molecular sieve: Guangdong Shengke Biochemical Technology Co., Ltd., content: silicon-aluminum ratio 60%, item number: CS999673.

[0055] Bentonite: Lingshou County Tuyun Mineral Products Processing Plant, product specifications: 800 mesh, item number: p-025.

[0056] Kaolin: Lingshou County Qiangdong Mineral Products Processing Plant, product specifications: 800 mesh, item number: qd-909.

[0057] Montmorillonite: Guangzhou Yifeng Chemical Technology Co., Ltd., particle size: 50 nm, model: TY-710C.

[0058] Polypropylene glycol: Hubei Xinkang Pharmaceutical Chemical Co., Ltd., product number: XK2412.

[0059] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0060] The design idea of ​​the present invention is to achieve high performance of potassium-doped tungsten rods for high-flexibility tungsten wire ropes by finely controlling the manufacturing process of doped tungsten rods, including key steps such as raw material selection, pre-reduction, vacuum spray doping, reduction, pickling, mixing, molding, pre-sintering and medium-frequency sintering. In particular, the introduction of functional agents in the preparation of dopant solutions aims to improve the uniformity and reactivity of doping elements, optimize the microstructure and macroscopic properties of tungsten rods, and thus significantly improve the flexibility, tensile strength, high-temperature stability and service life of tungsten wire ropes, ensuring better performance and longer service life in harsh application environments.

[0061] Example 1

[0062] A method for manufacturing a potassium-doped tungsten rod for high-flexibility tungsten wire rope is as follows:

[0063] Take the production of 800kg batch of tungsten wire rope with diameter 19*600mm as an example:

[0064] (1) Material selection

[0065] The weight ratio of monoclinic ammonium paratungstate to spherical ammonium paratungstate is 4:1.2, and the obtained mixture is used as a raw material;

[0066] (2) Pre-reduction

[0067] The raw material of step (1) was pre-reduced in a four-zone temperature reduction furnace, the temperatures of the four zones were 310°C, 400°C, 420°C, and 450°C, the boat load was 750 g, and the hydrogen flow rate was 0.3 m 3 / h, pushing speed 15min; passing through a 40-mesh sieve, 1036kg of ammonium tungsten bronze with cracks on the surface was obtained, wherein the cracks accounted for 85% of the total surface area of ​​the ammonium tungsten bronze;

[0068] (3) Vacuum spray doping

[0069] It is divided into four stages as follows:

[0070] In the first stage, 1036kg of sieved ammonia tungsten bronze was placed in a vacuum doping pot and evacuated to 350pa;

[0071] In the second stage, 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid and 2.17 kg of aluminum nitrate solids are respectively put into 60 L of deionized water at 60° C. to completely dissolve, and then 1 L of 4 mol / L dilute nitric acid is added, and the above solution is continuously stirred to prepare a dopant solution; the dopant solution is heated to 45° C., and then slowly sprayed from the atomization hole of the vacuum doping pot, and 1 / 4 of the atomization valve is opened, and 1 / 3 of the dopant solution is sprayed in within 1.5 hours, and the steam input valve is opened 1 / 3, the steam pressure is controlled to 0.15 MPa, and the vacuum pump output power is controlled to 30%. At this time, the material in the pot must be turned over, and the pot body is heated with steam to keep the temperature of the material in the furnace at 72° C.;

[0072] In the third stage, the frequency of the pot turning is increased, the temperature in the furnace is maintained at 90°C, and the remaining 2 / 3 of the doping agent is sprayed in by atomization within 40 minutes, the steam input valve is opened 2 / 3, the steam pressure is controlled at 0.15Mpa, and the vacuum pump output power is controlled at 30%;

[0073] In the fourth stage, after the atomization spraying of all dopants is completed, the steam input valve is fully opened, the steam pressure is controlled at 0.25Mpa, the temperature in the furnace is raised to 110°C, and the drying is continued for 3.5 hours to evaporate all the water. The output power of the vacuum pump is controlled to 80%. When the vacuum degree in the vacuum doping pot is maintained at 450Mpa, the steam heating is turned off, and water cooling is performed until the temperature in the furnace reaches 52°C. The discharge valve is opened to pass through a 40-mesh sieve to obtain 1041kg of potassium-ammonium tungsten bronze;

[0074] (4) Restore

[0075] Using a five-zone temperature reduction furnace, 1041 kg of potassium-ammonium-doped tungsten bronze obtained in step (3) was reduced once in a hydrogen atmosphere. The temperatures of the five temperature zones were 670°C, 725°C, 810°C, 830°C, and 860°C, respectively, and the hydrogen flow rate was 5m 3 / h, the boat loading is 450g, the effective reduction time is 7h, and 822kg of potassium-doped tungsten powder with an average particle size of 3.1μm is obtained, and the oxygen content of the powder is ≤700ppm;

[0076] The particle size distribution of the potassium-doped tungsten powder in the production state is as follows: the particle size D10 is 3.2 μm, the particle size D50 is 11.5 μm, and the particle size D90 is 28.5 μm; the particle size distribution of the potassium-doped tungsten powder in the grinding state is as follows: the particle size D10 is 1.8 μm, the particle size D50 is 3.8 μm, and the particle size D90 is 7.8 μm;

[0077] (5) Batch pickling

[0078] The 822 kg potassium-doped tungsten powder obtained in step (4) is washed with 4 mol / L dilute hydrochloric acid and 2 mL / L dilute hydrofluoric acid in turn to remove the ineffective potassium content and other impurities in the potassium-doped tungsten powder, and then the residual dilute hydrochloric acid and dilute hydrofluoric acid are removed with deionized water at 60° C. Finally, the tungsten mud is dried in a vacuum box, and then the dried tungsten mud is crushed again and passed through a 160-mesh sieve to finally obtain 814 kg of acid-washed potassium-doped tungsten powder with an effective potassium content of 72 ppm, Al≤20 ppm, Si≤20 ppm, and an oxygen content of ≤800 ppm;

[0079] (6) Mixing

[0080] 814 kg of acid-washed potassium-doped tungsten powder obtained in step (5) was placed in a high-speed mixer and mixed for 75 min under nitrogen protection. When cooled to 45° C., the powder was discharged and sieved through a 180-mesh sieve to obtain 809 kg of potassium-doped powder;

[0081] (7) Hard film cold isostatic pressing

[0082] According to the requirement of single weight of 3000g / piece, put it into a rubber hard mold sleeve with a length of 800mm, an inner diameter of 25mm and a thickness of 2mm, use mechanical vibration to put all 3000g of potassium-doped powder into the mold sleeve, vibrate it, seal it tightly, put it in a cold isostatic press, use a pressing pressure of 145Mpa, and obtain 268 pieces of potassium-doped tungsten green billets with a length of 670mm, a diameter of 22.5mm and good appearance, with a length rate of 100%;

[0083] (8) Low temperature impurity removal

[0084] The 268 potassium-doped tungsten green billets obtained in step (7) were placed in a hydrogen protection furnace at 1050° C. and fired for 50 min to obtain potassium-doped tungsten green billets with improved strength, without any breakage, and with a length rate of 100%;

[0085] (9) Vertical melting pre-sintering

[0086] The 268 potassium-doped tungsten blanks obtained in step (8) were placed in a vertical melting furnace for pre-sintering. Under the protection of hydrogen, the sintering was carried out by electricity to volatilize more than 95% of the impurities and reach an average density of 15.78 g / cm 3 The initial crystal size obtained from the cross section is 3.2nm, the appearance is dark gray, the upper and lower sections are uniformly crystallized, and there is no frame crystal;

[0087] The power-on sintering system is heating up, heating up, keeping warm, and keeping warm in sequence;

[0088] The current / time parameters are as follows: heating (0A~2800A) / 5min, heating (2800A~3850A) / 6min, heating (3850A~4820A) / 6min, keeping warm (4820A~4820A) / 21min;

[0089] Hydrogen flow rate is 2.0m 3 / h;

[0090] (10) Medium frequency sintering

[0091] The 268 incompletely dense potassium-doped tungsten bars obtained in step (9) are placed in a medium frequency furnace, and the tungsten bars are placed vertically in a stacking firing manner. The sintering is carried out under hydrogen protection by adopting a double hydrogen introduction method at the bottom and top of the furnace. The sintering process is automatically controlled by an infrared temperature measurement + PLC temperature control system; the sintering system is sequentially heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, and heat preservation; the temperature / time parameters are sequentially: (0-1250°C) / 430min, heat preservation: 1250°C / 90min, heating (12 Temperature (50~1500℃) / 150min, keep warm at 1500℃ / 120min, heat up (1500~1800℃) / 361min, keep warm at 1800℃ / 150min, heat up (1800~1900℃) / 180min, keep warm at 1900℃ / 150min, heat up (1900~2000℃) / 240min, keep warm at 2000℃ / 120min, heat up (2000~2050℃) / 180min, keep warm at 2050℃ / 300min.

[0092] The final potassium-doped tungsten rod has an average density of 18.35 g / cm 3 , potassium content is 58ppm, oxygen content is 8ppm, and the number of cross-section crystals is 29872 / mm 2 The average grain size is 12.8nm, reaching the micro-nano level.

[0093] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 88%-90%, a qualified rate of ≥95%, and a tensile strength of ≥2250N / mm 2 ; High temperature recrystallization temperature ≥1850℃, high temperature sag value of 0.39mm specification ≤1.5mm, aspect ratio ≥15, bending 90 degrees at room temperature and then straightening without cracking, the results of various parameters are better than the same type of potassium-doped tungsten wire on the market, winding 4*19*7 structure, good feedback; and according to statistics, the service life of the finished tungsten wire rope is more than 20% higher than the same type of products on the market.

[0094] Example 2

[0095] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0096] The preparation method of the dopant solution is as follows:

[0097] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then 1 L of 4 mol / L dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0098] The preparation method of the functional agent is as follows:

[0099] S1, 30g ZSM-5 molecular sieve was mixed with 40g bentonite, and then the mixture was added to 1500g 85wt% phosphoric acid solution for immersion treatment for 1 hour to promote the activation of the material surface; after the immersion process, the excess solution was removed by filtering and washing with water, followed by drying, and the dried powder was added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium were added for treatment; after the treatment was completed, the pretreated material was obtained by filtering, washing and drying;

[0100] S2, the pre-treated product obtained in step 1 is dispersed in 700g of water, and then 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of cobalt chloride are added to form a uniform precursor solution; the product is treated at 95°C and 0.3MPa for 2 hours, and then filtered, washed with water and dried, and then calcined at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0101] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0102] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0103] The final potassium-doped tungsten rod has an average density of 18.49 g / cm 3 , potassium content is 59ppm, oxygen content is 9ppm, and the number of cross-section crystals is 29946 / mm 2The average grain size is 11.6nm, reaching the micro-nano level.

[0104] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 90%-92%, a qualified rate of ≥97%, and a tensile strength of ≥2376N / mm 2 The high-temperature recrystallization temperature is ≥1880℃, the high-temperature sag value of 0.39mm specification is ≤1.2mm, the aspect ratio is ≥17, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 25% higher than that of the same type of products on the market.

[0105] Example 3

[0106] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0107] The preparation method of the dopant solution is as follows:

[0108] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then about 1 L of dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0109] The preparation method of the functional agent is as follows:

[0110] S1, 30g ZSM-5 molecular sieve is mixed with 40g kaolin, and then the mixture is added to 1500g 85wt% phosphoric acid solution for impregnation treatment for 1 hour to promote the activation of the material surface; after the impregnation process is completed, the excess solution is removed by filtering and washing with water, and then drying treatment is performed, and the dried powder is added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium are added for treatment; after the treatment is completed, the pretreated material is obtained by filtering, washing and drying;

[0111] S2, the pre-treated product obtained in step 1 is dispersed in 700g of water, and then 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of cobalt chloride are added to form a uniform precursor solution; the product is treated at 95°C and 0.3MPa for 2 hours, and then filtered, washed with water and dried, and then calcined at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0112] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0113] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0114] The potassium-doped tungsten rod finally obtained has an average density of 18.43g / cm 3 , potassium content is 57ppm, oxygen content is 8ppm, and the number of cross-section crystals is 29906 / mm 2 The average grain size is 12.1nm, reaching the micro-nano level.

[0115] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 89%-91%, a qualified rate of ≥95%, and a tensile strength of ≥2343N / mm 2 The high-temperature recrystallization temperature is ≥1872℃, the high-temperature sag value of 0.39mm specification is ≤1.3mm, the aspect ratio is ≥15, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 23% higher than that of the same type of products on the market.

[0116] Example 4

[0117] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0118] The preparation method of the dopant solution is as follows:

[0119] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then about 1 L of dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0120] The preparation method of the functional agent is as follows:

[0121] S1, 30g ZSM-5 molecular sieve and 40g montmorillonite were mixed, and then the mixture was added to 1500g 85wt% phosphoric acid solution for impregnation treatment for 1 hour to promote the activation of the material surface; after the impregnation process, the excess solution was removed by filtering and washing with water, followed by drying treatment, and the dried powder was added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium were added for treatment; after the treatment was completed, the pretreated material was obtained by filtering, washing and drying;

[0122] S2, the pre-treated product obtained in step 1 is dispersed in 700g of water, and then 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of cobalt chloride are added to form a uniform precursor solution; the product is treated at 95°C and 0.3MPa for 2 hours, and then filtered, washed with water and dried, and then calcined at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0123] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0124] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0125] The final potassium-doped tungsten rod has an average density of 18.42 g / cm 3 , potassium content is 57ppm, oxygen content is 8ppm, and the number of cross-section crystals is 29908 / mm 2 The average grain size is 12.2nm, reaching the micro-nano level.

[0126] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 89%-91%, a qualified rate of ≥95%, and a tensile strength of ≥2362N / mm 2 The high-temperature recrystallization temperature is ≥1865℃, the high-temperature sag value of 0.39mm specification is ≤1.3mm, the aspect ratio is ≥16, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 22% higher than that of the same type of products on the market.

[0127] Example 5

[0128] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0129] The preparation method of the dopant solution is as follows:

[0130] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then about 1 L of dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0131] The preparation method of the functional agent is as follows:

[0132] S1, 30g ZSM-5 molecular sieve was mixed with 40g bentonite, and then the mixture was added to 1500g 85wt% phosphoric acid solution for immersion treatment for 1 hour to promote the activation of the material surface; after the immersion process, the excess solution was removed by filtering and washing with water, followed by drying, and the dried powder was added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium were added for treatment; after the treatment was completed, the pretreated material was obtained by filtering, washing and drying;

[0133] S2, the pre-treated product obtained in step 1 is dispersed in 700g of water, and then 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of nickel nitrate are added to form a uniform precursor solution; the product is treated at 95°C and 0.3MPa for 2 hours, and then filtered, washed with water and dried, and then calcined at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0134] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0135] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0136] The potassium-doped tungsten rod finally obtained has an average density of 18.39g / cm 3 , potassium content is 58ppm, oxygen content is 8ppm, and the number of cross-section crystals is 29913 / mm 2 The average grain size is 12.4nm, reaching the micro-nano level.

[0137] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 89%-91%, a qualified rate of ≥96%, and a tensile strength of ≥2335N / mm 2 The high-temperature recrystallization temperature is ≥1869℃, the high-temperature sag value of 0.39mm specification is ≤1.3mm, the aspect ratio is ≥15, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 23% higher than that of the same type of products on the market.

[0138] Example 6

[0139] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0140] The preparation method of the dopant solution is as follows:

[0141] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then about 1 L of dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0142] The preparation method of the functional agent is as follows:

[0143] S1, 30g ZSM-5 molecular sieve was mixed with 40g bentonite, and then the mixture was added to 1500g 85wt% phosphoric acid solution for immersion treatment for 1 hour to promote the activation of the material surface; after the immersion process, the excess solution was removed by filtering and washing with water, followed by drying, and the dried powder was added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium were added for treatment; after the treatment was completed, the pretreated material was obtained by filtering, washing and drying;

[0144] S2, dispersing the pre-treated product obtained in step 1 in 700g of water, then adding 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of zinc nitrate to form a uniform precursor solution; treating at 95°C and 0.3MPa for 2 hours, then filtering, washing with water and drying, and then calcining at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0145] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0146] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0147] The potassium-doped tungsten rod finally obtained has an average density of 18.40g / cm 3 , potassium content is 59ppm, oxygen content is 8ppm, and the number of cross-section crystals is 29911 / mm 2 The average grain size is 12.4nm, reaching the micro-nano level.

[0148] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 90%-92%, a qualified rate of ≥96%, and a tensile strength of ≥2350N / mm 2 The high-temperature recrystallization temperature is ≥1878℃, the high-temperature sag value of 0.39mm specification is ≤1.4mm, the aspect ratio is ≥16, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 23% higher than that of the same type of products on the market.

[0149] Example 7

[0150] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being the method for preparing the dopant solution in the second stage of step (3).

[0151] The preparation method of the dopant solution is as follows:

[0152] 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid, 2.17 kg of aluminum nitrate solid, and 0.2 kg of functional agent were respectively put into 60 L of deionized water at 60° C. and completely dissolved, and then about 1 L of dilute nitric acid was added and the above solution was continuously stirred to prepare a dopant solution.

[0153] The preparation method of the functional agent is as follows:

[0154] S1, 30g ZSM-5 molecular sieve was mixed with 40g bentonite, and then the mixture was added to 1500g 85wt% phosphoric acid solution for immersion treatment for 1 hour to promote the activation of the material surface; after the immersion process, the excess solution was removed by filtering and washing with water, followed by drying, and the dried powder was added to 1800g 70wt% ethanol aqueous solution for mixing, and then 6g 1-octylpyridinium bromide and 10g EDTA disodium calcium were added for treatment; after the treatment was completed, the pretreated material was obtained by filtering, washing and drying;

[0155] S2, the pre-treated product obtained in step 1 is dispersed in 700g of water, and then 30g of tetraallyl silicate, 60g of diethylenetriamine and 3g of manganese sulfate are added to form a uniform precursor solution; the product is treated at 95°C and 0.3MPa for 2 hours, and then filtered, washed with water and dried, and then calcined at 400°C under a nitrogen atmosphere for 4 hours to obtain a post-treated product;

[0156] S3, dissolving 40g of poly 1,2-propylene glycol and 30g of methyl acetoacetate in 700g of water to form a uniform solution; adding 2g of 80wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 90°C, and the treatment time is 6 hours; collecting the liquid in the reactor to obtain a promoter;

[0157] S4, 40g of the post-processed product obtained in step S2 is mixed with 150g of the accelerator obtained in step S3, the pH value is adjusted to 10 by 15wt% ammonia water, the mixture is treated for 2 hours, and then the pH value is adjusted to 8.5 by ammonia evaporation to obtain a functional agent.

[0158] The potassium-doped tungsten rod finally obtained has an average density of 18.48g / cm 3 , potassium content is 58ppm, oxygen content is 9ppm, and the number of cross-section crystals is 29915 / mm 2 The average grain size is 12.5nm, reaching the micro-nano level.

[0159] The potassium-doped tungsten rod of this embodiment is processed into tungsten wires of different specifications of 0.3mm-0.6mm, with a finished product rate of 90%-92%, a qualified rate of ≥96%, and a tensile strength of ≥2353N / mm 2 The high-temperature recrystallization temperature is ≥1879℃, the high-temperature sag value of 0.39mm specification is ≤1.3mm, the aspect ratio is ≥16, and there is no cracking when it is bent 90 degrees and then straightened at room temperature. The results of various parameters are better than the same type of potassium-doped tungsten wire on the market. The winding structure is 4*19*7, and the feedback is good. According to statistics, the service life of the finished tungsten wire rope is more than 23% higher than that of the same type of products on the market.

[0160] Comparative Example 1

[0161] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is substantially the same as that of Example 1, the only difference being that in step (1), monoclinic ammonium paratungstate and spherical ammonium paratungstate are mixed in a weight ratio of 4:0.9.

[0162] The final potassium-doped tungsten rod has an average density of 17.92 g / cm 3 , potassium content is 56ppm, oxygen content is 8ppm, and the number of cross-section crystals is 10872 / mm 2 , the average grain size is 21.2nm.

[0163] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 68% to 72%, and the qualified rate is 52.8%≤78.3%, 980N / mm 2 ≤Tensile strength≤1850N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bent 90 degrees at room temperature and then straightened, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0164] Comparative Example 2

[0165] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in step (1), monoclinic ammonium paratungstate and spherical ammonium paratungstate are mixed in a weight ratio of 4:1.6.

[0166] The final potassium-doped tungsten rod has an average density of 16.92 g / cm 3 , potassium content is 62ppm, oxygen content is 10ppm, and the number of cross-section crystals is 10928 / mm 2 , the average grain size is 21.6nm.

[0167] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 69% to 74%, 55.1%≤qualified rate≤78.9%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0168] It can be seen from Example 1 and Comparative Examples 1-2 that the morphology of ammonium paratungstate has a great influence on the performance of subsequent tungsten oxide, tungsten powder and tungsten carbide. By mixing ammonium paratungstates of different crystalline forms as raw materials, coarse and fine doped tungsten powders can be directly reduced by a subsequent special reduction process to obtain a mixed batch with a good normal distribution, while avoiding the mixed tungsten powder with a spike shape or a double peak phenomenon, so that the tungsten wire after the tungsten bar processing has excellent performance.

[0169] Comparative Example 3

[0170] A method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that step (2) obtains ammonium tungsten bronze with cracks on the surface, wherein the cracks account for 74% of the total surface area of ​​the ammonium tungsten bronze.

[0171] The potassium-doped tungsten rod finally obtained has an average density of 15.92g / cm 3 , potassium content is 80ppm, oxygen content is 10ppm, and the number of cross-section crystals is 12928 / mm 2 , the average grain size is 17.5nm.

[0172] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 68% to 72%, 55.2%≤qualified rate≤78.1%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0173] It can be seen from Example 1 and Comparative Example 3 that the specific process conditions are used to pre-reduce ammonium paratungstate into a special intermediate ammonium tungsten bronze (ATB). Since ATB has many fine cracks, it is beneficial for the dopant solution to penetrate deep into the interior. In addition, the appropriate amount of NH 4+ It is also beneficial to K + The addition of ATB, together with its good surface activity, effectively solves the problems of low density, small grain size, difficult processing, low yield rate, deterioration of organizational structure, high plastic-brittle transition temperature, and poor high-temperature anti-sagging performance of tungsten bars obtained by conventional methods.

[0174] Comparative Example 4

[0175] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that the amount of potassium hydroxide added to the second-stage dopant solution in step (3) is 2 kg.

[0176] The final potassium-doped tungsten rod has an average density of 15.28 g / cm 3 , potassium content is 63ppm, oxygen content is 9ppm, and the number of cross-section crystals is 9896 / mm 2 , the average grain size is 25.1nm.

[0177] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 69% to 74%, 55.1%≤qualified rate≤78.9%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0178] Comparative Example 5

[0179] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that the amount of potassium hydroxide added to the second-stage dopant solution in step (3) is 2.5 kg.

[0180] The final potassium-doped tungsten rod has an average density of 18.0g / cm 3 , potassium content is 81ppm, oxygen content is 8ppm, and the number of cross-section crystals is 10105 / mm 2 , the average grain size is 21.5nm.

[0181] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 69% to 74%, 55.1%≤qualified rate≤78.9%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0182] Comparative Example 6

[0183] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in the second-stage dopant solution of step (3), the amount of silicate added is 4.6 kg.

[0184] The final potassium-doped tungsten rod has an average density of 14.92g / cm 3 , potassium content is 65ppm, oxygen content is 10ppm, and the number of cross-section crystals is 10743 / mm 2 , the average grain size is 18.7nm.

[0185] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 65% to 72%, 55.1%≤qualified rate≤78.9%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 980℃≤high temperature recrystallization temperature≤1250℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0186] Comparative Example 7

[0187] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in the second-stage dopant solution of step (3), the amount of silicate added is 5.4 kg.

[0188] The final potassium-doped tungsten rod has an average density of 17.09 g / cm 3 , potassium content is 63ppm, oxygen content is 10ppm, and the number of cross-section crystals is 10928 / mm 2 , the average grain size is 21.6nm.

[0189] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 68% to 72%, the qualified rate is 54.9%≤72.7%, and the 975N / mm 2 ≤Tensile strength≤1480N / mm 2 ; 1000℃≤high temperature recrystallization temperature≤1050℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0190] Comparative Example 8

[0191] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in the second-stage dopant solution of step (3), the amount of aluminum nitrate added is 1.9 kg.

[0192] The potassium-doped tungsten rod finally obtained has an average density of 16.82g / cm 3 , potassium content is 65ppm, oxygen content is 10ppm, and the number of cross-section crystals is 9825 / mm 2 , the average grain size is 20.9nm.

[0193] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 63% to 71%, 56.2%≤qualified rate≤74.3%, 850N / mm 2 ≤Tensile strength≤1580N / mm 2 ; 1050℃≤high temperature recrystallization temperature≤1250℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0194] Comparative Example 9

[0195] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in the second-stage dopant solution of step (3), the amount of aluminum nitrate added is 2.3 kg.

[0196] The final potassium-doped tungsten rod has an average density of 16.75g / cm 3 , potassium content is 62ppm, oxygen content is 10ppm, and the number of cross-section crystals is 10121 / mm 2 , the average grain size is 21.6nm.

[0197] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 69% to 74%, 55.1%≤qualified rate≤78.9%, 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1060℃≤high temperature recrystallization temperature≤1250℃, high temperature sag value of 4.2mm≤0.39mm specification≤5.8mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0198] It can be seen from Example 1 and Comparative Examples 4 to 9 that the present invention uses potassium hydroxide, silicic acid, and aluminum nitrate to prepare a mixed solution of potassium silicate and aluminum nitrate, in which elements such as aluminum and silicon can promote the entry of potassium into the tungsten matrix, thereby significantly reducing the low-temperature brittleness of the tungsten wire and reducing the splitting of the tungsten wire, so that the prepared tungsten wire has good high-temperature anti-sagging performance.

[0199] Comparative Example 10

[0200] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, except that step (3) is divided into three stages:

[0201] The first stage is the same as in Example 1;

[0202] In the second stage, 2.31 kg of potassium hydroxide, 5.03 kg of silicic acid and 2.17 kg of aluminum nitrate solids are respectively put into 60 L of deionized water at 60° C. to completely dissolve, and then 1 L of dilute nitric acid is added, and the above solution is continuously stirred to prepare a dopant solution; the dopant solution is heated to 45° C., and then slowly sprayed from the atomization hole of the vacuum doping pot, and 1 / 4 of the atomization valve is opened, and 1 / 3 of the dopant solution is sprayed in within 1.5 hours, and the steam input valve is opened 1 / 3, the steam pressure is controlled to 0.15 Mpa, and the vacuum pump output power is controlled to 30%. At this time, the material in the pot must be turned over, and the pot body is heated with steam to keep the temperature of the material in the furnace at 90° C.;

[0203] In the third stage, the temperature in the furnace is raised to 110°C to evaporate all the water to obtain potassium-ammonium-doped tungsten bronze.

[0204] The potassium-doped tungsten rod finally obtained has an average density of 12.92g / cm 3 , potassium content is 58ppm, oxygen content is 10ppm, and the number of cross-section crystals is 8762 / mm 2 , the average grain size is 35.9nm.

[0205] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 62% to 70%, 52.1%≤qualified rate≤71.9%, 905N / mm 2 ≤Tensile strength≤1120N / mm 2 ; 789℃≤high temperature recrystallization temperature≤1050℃, high temperature sag value of 4.8mm≤0.39mm specification≤6.9mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0206] Comparative Example 11

[0207] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference is that low-power vacuuming is used in the second, third and fourth stages of step (3), and the output power of the vacuum pump is controlled to 30%.

[0208] The final potassium-doped tungsten rod has an average density of 13.82 g / cm 3, potassium content is 59ppm, oxygen content is 10ppm, and the number of cross-section crystals is 10252 / mm 2 , the average grain size is 28.6nm.

[0209] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 63% to 70%, the qualified rate is 54.8%≤72.5%, and the 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 985℃≤high temperature recrystallization temperature≤1050℃, high temperature sag value of 4.9mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0210] Comparative Example 12

[0211] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, with the only difference being that the effective reduction time in step (4) is 5.5 hours.

[0212] The final potassium-doped tungsten rod has an average density of 14.37 g / cm 3 , potassium content is 60ppm, oxygen content is 8ppm, and the number of cross-section crystals is 9043 / mm 2 , the average grain size is 25.0nm.

[0213] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 65% to 69%, the qualified rate is 55.2%≤75.8%, and the 985N / mm 2 ≤Tensile strength≤1780N / mm 2 ; 1020℃≤high temperature recrystallization temperature≤1200℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0214] Comparative Example 13

[0215] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, with the only difference being that the effective reduction time in step (4) is 8.5 hours.

[0216] The final potassium-doped tungsten rod has an average density of 16.34 g / cm 3 , potassium content is 60ppm, oxygen content is 8ppm, and the number of cross-section crystals is 8726 / mm 2, the average grain size is 22.2nm.

[0217] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 65% to 72%, 52.2%≤ qualified rate≤76.9%, 920N / mm 2 ≤Tensile strength≤1680N / mm 2 ; 980℃≤high temperature recrystallization temperature≤1250℃, high temperature sag value of 4.5mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0218] Comparative Example 14

[0219] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in step (8), the potassium-doped tungsten green body is placed in a hydrogen protection furnace at 980° C. and fired for 50 minutes.

[0220] The potassium-doped tungsten rod finally obtained has an average density of 12.92g / cm 3 , potassium content is 58ppm, oxygen content is 10ppm, and the number of cross-section crystals is 7909 / mm 2 , the average grain size is 22.0nm.

[0221] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 698% to 71%, 54.1%≤qualified rate≤78.9%, 965N / mm 2 ≤Tensile strength≤1580N / mm 2 ; 1080℃≤high temperature recrystallization temperature≤1350℃, high temperature sag value of 3.8mm≤0.39mm specification≤5.5mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0222] Comparative Example 15

[0223] The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that in step (8), the potassium-doped tungsten green body is placed in a hydrogen protection furnace at 1150° C. and fired for 50 minutes.

[0224] The final potassium-doped tungsten rod has an average density of 16.44 g / cm 3 , potassium content is 61ppm, oxygen content is 9ppm, and the number of cross-section crystals is 10928 / mm 2 , the average grain size is 21.6nm.

[0225] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 64% to 72%, 52.1%≤qualified rate≤72.9%, 965N / mm 2 ≤Tensile strength≤1280N / mm 2 ; 980℃≤high temperature recrystallization temperature≤1050℃, high temperature sag value of 4.2mm≤0.39mm specification≤5.9mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0226] Comparative Example 16

[0227] A method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that the step (9) vertical melting pre-sintering + the step (10) medium frequency sintering are replaced by vertical melting sintering, and under hydrogen protection, the vertical melting sintering is carried out according to the following vertical melting sintering system (current / time): heating (0A-2900A) / 5min, heating (2900A-3950A) / 6min, heating (3950A-4950A) / 6min, and keeping warm at 4950A / 21min;

[0228] The potassium-doped tungsten rod finally obtained has an average density of 12.81g / cm3, a potassium content of 60ppm, an oxygen content of 8ppm, a cross-sectional crystal number of 8206 / mm2, and an average grain size of 21.5nm.

[0229] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 62% to 72%, 52.1%≤qualified rate≤69.9%, 915N / mm 2 ≤Tensile strength≤1230N / mm 2 ; 780℃≤high temperature recrystallization temperature≤1080℃, high temperature sag value of 4.3mm≤0.39mm specification≤5.8mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0230] Comparative Example 17

[0231] A method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope is basically the same as that in Example 1, the only difference being that the vertical melting pre-sintering in step (9) and the medium frequency sintering in step (10) are replaced by medium frequency sintering, and the sintering schedule of the medium frequency sintering is heating, heat preservation, heating, heat preservation, heating, heat preservation, heating, heat preservation, heating, heat preservation, heating, heat preservation, and heat preservation; the temperature / time parameters are in sequence: heating (0-1350°C) / 430min, heat preservation at 1350°C / 9min, heating (1350-160 ... / 150min, keep warm at 1600℃ / 180min, heat up (1600~1850℃) / 361min, keep warm at 1850℃ / 180min, heat up (1850~2050℃) / 180min, keep warm at 2050℃ / 180min, heat up (2050~2300℃) / 240min, keep warm at 2300℃ / 120min, heat up (2300~2650℃) / 180min, keep warm at 2650℃ / 300min.

[0232] The potassium-doped tungsten rod finally obtained has an average density of 16.09g / cm 3 , potassium content is 58ppm, oxygen content is 10ppm, and the number of cross-section crystals is 9528 / mm 2 , the average grain size is 21.8nm.

[0233] The potassium-doped tungsten rod of this comparative example is processed into tungsten wires of different specifications of 0.3mm to 0.6mm, and the finished product rate is 61% to 70%, 51.0%≤qualified rate≤72.5%, 905N / mm 2 ≤Tensile strength≤1080N / mm 2 ; 980℃≤high temperature recrystallization temperature≤1050℃, high temperature sag value of 4.2mm≤0.39mm specification≤6.0mm, aspect ratio≤12, cracking occurs when bending 90 degrees at room temperature and then straightening, winding 4*19*7 structure, the service life of the finished tungsten wire rope is not significantly different from the same type of products on the market.

[0234] It can be seen from Example 1 and Comparative Examples 16 to 17 that the present invention adopts vertical melting pre-sintering + medium frequency sintering. According to the formation mechanism of potassium bubbles, the number of grains in the cross section of the tungsten bar is increased and the local growth of grains is avoided, thereby achieving the purpose of small potassium bubble pore size, high density, many grain boundaries, long potassium bubble columns and uniform distribution. The potassium bubbles have a large aspect ratio and good high temperature anti-droop performance.

[0235] In summary, it can be seen from Example 1 and Comparative Examples 1 to 17 that the present invention starts from multiple factors and coordinates to control and balance the relationship between the density and crystallization of the potassium-doped tungsten rod to obtain a high-density and micron-crystalline potassium-doped tungsten rod, so that the tungsten wire made of this tungsten rod has high-temperature creep resistance and high strength, a higher recrystallization temperature, and stable toughness, effectively improving the processing problems of low tungsten wire finished product rate and low yield, and further enabling the tungsten wire to obtain excellent high-temperature strength, high-temperature anti-sagging performance and anti-deformation performance, and reducing the processing cost of rods and wires, saving energy and reducing consumption.

[0236] The introduction of the functional agent in Example 2 significantly improves the performance of the potassium-doped tungsten rod compared to Example 1 without adding the functional agent. This is mainly because the functional agent enhances the uniform dispersion of the components in the dopant solution on the surface of tungsten bronze, promotes the effective expansion between montmorillonite layers, increases active sites, refines grains, optimizes the distribution of doping elements, improves sintering behavior, improves reduction efficiency, and enhances the stability of the material in high temperature and chemically active environments, so that the final product has a higher density, a more uniform microstructure and better mechanical properties. These combined effects work together to improve the finished product rate, qualified rate and service life of the tungsten wire rope, giving it a competitive advantage in the market.

[0237] In Example 2 of the present invention, the bentonite used as the functional agent can bring better results than the kaolin in Example 3 and the montmorillonite in Example 4, probably because of the unique physical and chemical properties of bentonite. Bentonite has a higher cation exchange capacity and a larger specific surface area, which enables it to more effectively promote the activation of the material surface during the impregnation process and enhance the interaction with other components in the solution. In addition, the layered structure of bentonite may be more conducive to the formation of a multi-level pore structure during hydrothermal treatment and calcination, thereby increasing the dispersibility and accessibility of the active components in the dopant solution, and improving the doping efficiency and uniformity. The combined effect of these characteristics makes the doped tungsten bars show better results in both microstructure and macroscopic properties, such as higher density, finer grain size and more optimized physical properties. Therefore, the use of bentonite in the preparation of functional agents provides a key boost to improving the overall quality of doped tungsten bars.

[0238] In multiple embodiments of the present invention, the selection of functional agents for the dopant solution has a significant effect on the performance of the final potassium-doped tungsten rod. In particular, the cobalt chloride used in Example 2 exhibits superior performance compared to the nickel nitrate of Example 5, the zinc nitrate of Example 6, and the manganese sulfate of Example 7. This difference may be due to the unique catalytic activity of cobalt chloride, which promotes more efficient reaction kinetics during the doping process and helps to form a more uniform doping distribution. In addition, cobalt chloride may promote the formation of stable complexes, improve grain growth control during sintering, and optimize the microstructure, thereby improving the mechanical properties and high-temperature stability of the material. These combined effects enable the doped tungsten rod to achieve a better balance in key parameters such as density, potassium content, oxygen content, and grain size, ultimately resulting in an improvement in the yield, pass rate, tensile strength, and high-temperature performance of the doped tungsten rod, meeting the stringent material requirements of high-flexibility tungsten wire ropes.

[0239] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope, characterized in that: Here’s how: (1) Material selection Monoclinic ammonium paratungstate is mixed with spherical ammonium paratungstate, and the obtained mixture is used as a raw material; (2) Pre-reduction The raw material of step (1) is pre-reduced using a reduction furnace with no less than four temperature zones to obtain ammonium tungsten bronze with cracks on the surface; The raw material of step (1) is reduced by using a four-zone temperature reduction furnace to obtain ammonium tungsten bronze with cracks on the surface; (3) Vacuum spray doping It is divided into four stages: In the first stage, an appropriate amount of ammonium tungsten bronze obtained in step (2) is placed in a vacuum doping pot and evacuated to ≤500 Pa; In the second stage, potassium hydroxide, silicic acid and aluminum nitrate solids are respectively put into water at 50-70°C to completely dissolve, and then dilute nitric acid is added, and the above solutions are continuously stirred to prepare a doping agent solution, and the temperature of the doping agent solution is heated to 40-50°C, and then slowly sprayed from the atomization hole of the vacuum doping pot, and the total amount does not exceed 1 / 3 of the rated addition amount, and the steam input valve is opened 1 / 3, and the steam pressure is controlled to be 0.1-0.2Mpa, and at this time, the materials in the pot must be turned over, and the pot body is heated with steam to keep the temperature of the materials in the furnace at 55-85°C; In the third stage, the frequency of the pot body turning is increased, and the remaining dopant solution is sprayed in atomization within 30 to 50 minutes, the temperature in the furnace is maintained at 85 to 95°C, the steam input valve is opened 2 / 3, and the steam pressure is controlled at 0.1 to 0.2Mpa; In the fourth stage, after the atomization spraying of all dopants is completed, the steam input valve is fully opened, the steam pressure is controlled at 0.2-0.3Mpa, the temperature in the furnace is raised to 100-120°C, and the drying is continued for 3.5 hours to evaporate all the water. When the vacuum degree in the vacuum doping pot is maintained at 400-500Mpa, the steam heating is turned off, and water cooling is performed until the temperature in the furnace reaches 50-55°C. The discharge valve is opened to pass through a 20-100 mesh sieve to obtain potassium-ammonium-doped tungsten bronze; (4) Restore The potassium-ammonium-doped tungsten bronze obtained in step (3) is reduced once in a hydrogen atmosphere to obtain potassium-doped tungsten powder with an average particle size of 3.0 μm to 3.2 μm; The production state particle size distribution of the potassium-doped tungsten powder has a particle size D10 of 3.1 μm to 3.6 μm, a particle size D50 of 8.0 μm to 15 μm, and a particle size D90 of 25 μm to 32 μm; The ground particle size distribution of the potassium-doped tungsten powder is such that the particle size D10 is 1.5 μm to 2.1 μm, the particle size D50 is 3.4 μm to 4.1 μm, and the particle size D90 is 6.5 μm to 8.2 μm; (5) Batch pickling The potassium-doped tungsten powder obtained in step (4) is washed with 4 mol / L dilute hydrochloric acid and 2 mL / L dilute hydrofluoric acid in sequence to remove invalid potassium and other impurities in the potassium-doped tungsten powder, and then the residual dilute hydrochloric acid and dilute hydrofluoric acid are removed with water at a temperature of 50° C. to 65° C., and finally the tungsten mud is dried in a vacuum box, and the dried tungsten mud is crushed again and passed through a sieve to obtain acid-washed potassium-doped tungsten powder; (6) Mixing The acid-washed potassium-doped tungsten powder obtained in step (5) is put into a high-speed mixer, mixed for 60 to 120 minutes under the protection of nitrogen, and discharged and sieved through a 150 to 200 mesh sieve when cooled to 40 to 50° C. to obtain a potassium-doped mixed powder; (7) Hard film cold isostatic pressing The potassium-doped powder obtained in step (6) is placed in a rubber hard mold sleeve with a length of 800 mm, a diameter of 25.5 mm to 27 mm, and a wall thickness of 1.8 mm to 2.2 mm according to a unit weight of 3000 g / piece to 4000 g / piece, and is vibrated and sealed and fastened. The mold sleeve is placed in a cold isostatic press and a pressing pressure of 140 MPa to 170 MPa is used to obtain a potassium-doped tungsten green body with good appearance and certain strength. (8) Low temperature impurity removal The potassium-doped tungsten green body obtained in step (7) is placed in a hydrogen protection furnace at 1000° C. to 1100° C. and fired for 40 min to 60 min to obtain a potassium-doped tungsten green body with improved strength; (9) Vertical melting pre-sintering The potassium-doped tungsten blank obtained in step (8) is placed in a vertical melting furnace and sintered under hydrogen protection to volatilize more than 95% of the impurities and reach a density of 15.5 g / cm 3 ~16.5g / cm 3 , the initial crystal size obtained in the cross section is 1.5nm~5nm; The power-on sintering system is heating up, heating up, keeping warm, and keeping warm in sequence; The current / time parameters are as follows: heating 0A~2800A / 5min, heating 2800A~3850A / 6min, heating 3850A~4820A / 6min, keeping warm 4820A~4820A / 21min; hydrogen flow rate is 1.8m 3 / h~2.2m 3 / h; (10) Medium frequency sintering The incompletely dense potassium-doped tungsten bars obtained in step (9) are placed in a medium frequency furnace, and the tungsten bars are placed vertically in a stacking firing mode. The sintering is carried out under hydrogen protection by adopting a double hydrogen introduction mode at the bottom and top of the furnace. The sintering process is automatically controlled by an infrared temperature measurement + PLC temperature control system. The sintering system is sequentially heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, heating up, heat preservation, and heat preservation. The temperature / time parameters are sequentially: (0-1250°C) / 430min, heat preservation: 1250°C / 90min, heating (1250 ~1500℃) / 150min, keep warm at 1500℃ / 120min, heat up (1500~1800℃) / 361min, keep warm at 1800℃ / 150min, heat up (1800~1900℃) / 180min, keep warm at 1900℃ / 150min, heat up (1900~2000℃) / 240min, keep warm at 2000℃ / 120min, heat up (2000~2050℃) / 180min, keep warm at 2050℃ / 300min.

2. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: In the material selection of step (1), monoclinic ammonium paratungstate and spherical ammonium paratungstate are mixed in a weight ratio of 4:1 to 1.

5.

3. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: The ammonium tungsten bronze with cracks during the pre-reduction in step (2), wherein the cracks account for more than 75% of the total surface area of ​​the ammonium tungsten bronze.

4. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: In the step (2), the temperatures of the four temperature zones in the pre-reduction are 300°C to 330°C, 390°C to 410°C, 410°C to 430°C, and 430°C to 450°C, respectively, and the hydrogen flow rate is 0.3m 3 / h~0.4m 3 / h, the pre-reduction boat load is 720g-800g, passed through a 20-100 mesh sieve, and pushed at a speed of 10-20min.

5. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: In the second stage of the vacuum spray doping in step (3), the contents of various substances are 2 to 3 parts by weight of potassium hydroxide, 4.5 to 5.5 parts by weight of silicic acid, and 1.8 to 3 parts by weight of aluminum nitrate solids, which are completely dissolved in 50 to 70 L of water at 50 to 70° C., and then 0.5 to 2 L of dilute nitric acid is added.

6. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: In the step (3) of vacuum spray doping, low power is used for vacuuming in the second stage, the third stage and the initial stage of the fourth stage, and medium-high power is used for vacuuming in the middle and late stages of the fourth stage; wherein the low power is 25% to 35% of the output power of the vacuuming equipment, and the medium-high power is 70% to 85% of the output power of the vacuuming equipment.

7. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: The temperatures of the five temperature zones in the reduction step (4) are 660°C to 680°C, 710°C to 740°C, 790°C to 820°C, 820°C to 840°C, and 840°C to 870°C, respectively, and the hydrogen flow rate is 4m 3 / h~7m 3 / h, the boat loading amount is 350g ~ 550g, and the effective reduction time is 6h ~ 8h.

8. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 1, characterized in that: In the step (5), the batch is pickled and passed through a 150-170 mesh screen to obtain an acid-washed potassium-doped tungsten powder, wherein the effective potassium content of the acid-washed potassium-doped tungsten powder is 65ppm-80ppm.

9. The method for manufacturing a potassium-doped tungsten rod for a high-flexibility tungsten wire rope according to claim 5, characterized in that: In the second stage of the vacuum spray doping in step (3), the contents of the substances are 2-3 parts by weight of potassium hydroxide, 4.5-5.5 parts by weight of silicic acid, 1.8-3 parts by weight of aluminum nitrate solid, and 0.1-0.3 parts by weight of a functional agent, which are completely dissolved in 50-70 L of water at 50-70° C., and then 0.5-2 L of dilute nitric acid is added; The preparation method of the functional agent is as follows, in parts by weight: S1, 25-35 parts of ZSM-5 molecular sieve and 35-45 parts of bentonite are mixed, and then the mixture is added to 1400-1600 parts of 80-90wt% phosphoric acid solution for impregnation treatment for 0.5-2 hours to promote the activation of the material surface; after the impregnation process is completed, the excess solution is removed by filtering and washing with water, and then drying is performed, and the dried powder is added to 1700-1900 parts of 60-80wt% ethanol aqueous solution for mixing, and then 5-7 parts of 1-octylpyridinium bromide and 8-12 parts of EDTA disodium calcium are added for treatment; after the treatment is completed, the pretreated product is obtained by filtering, washing and drying; S2, dispersing the pretreated product obtained in step 1 in 600-800 parts of water, then adding 25-35 parts of tetraallyl silicate, 55-65 parts of diethylenetriamine and 2-4 parts of cobalt chloride to form a uniform precursor solution; treating at 90-98°C and 0.2-0.4MPa for 1-3 hours, then filtering, washing with water and drying, and then calcining at 300-500°C under a nitrogen atmosphere for 2-5 hours to obtain a post-treated product; S3, dissolving 35-45 parts of poly 1,2-propylene glycol and 25-35 parts of methyl acetoacetate in 600-800 parts of water to form a uniform solution; adding 1-3 parts of 70-85wt% sulfuric acid, under nitrogen protection, the temperature is controlled at 80-95°C, and the treatment time is 3-10 hours; collecting the liquid in the reactor to obtain a promoter; S4, 30 to 50 parts of the post-treated product obtained in step S2 are mixed with 140 to 160 parts of the accelerator obtained in step S3, the pH value is adjusted to 9 to 10.5 by 10 to 18 wt % ammonia water, the treatment is carried out for 1 to 3 hours, and then the pH value is adjusted to 8 to 9 by ammonia evaporation treatment to obtain a functional agent.

10. A potassium-doped tungsten rod for high-flexibility tungsten wire rope, characterized in that: The method is manufactured by the manufacturing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of wolfram filament for halogen tungsten lamp

    CN101157997A

  • Method for producing tungsten bar serving as halogen tungsten lamp tungsten filament

    CN102198507A

  • Preparation method for micro-lanthanum-doped tungsten wire

    CN102424941A

  • Preparation method of potassium-containing round-tungsten-doped aluminum strip

    CN102672175A

  • Production method of potassium-dopedmetal tungsten powder and method for producing tungsten bar through tungsten powder

    CN105903977A

Cited By

  • Low-potassium doped molybdenum powder and preparation method and application thereof

    CN122007398A